User-Friendly Locations of Error Messages in Web Forms: An Eye Tracking Study - Yavuz Inal (Journal of Eye Movement Research)
Error messages presented to users are one of the most important elements of Web forms. Error messages are embedded in different parts of the forms available on the Internet and presented in various formats. One of the measures of a user-friendly error message design is the ability to easily capture users’ attention and facilitate fast error correction. In this empirical study, I tested four different locations of error messages frequently used in Web forms on 32 participants. In addition, I analysed the participants’ interactions with error messages through their eye movements. The results of the study showed that the participants spotted the error message fastest when it was displayed on the right side of the erroneous input field. When error messages displayed further the input field users have less saccades to and fixations on error messages compared to those located near to this field, suggesting that less effort has been spent to understand the given message. However, group mean dif-ferences were not statistically significant for form completion time, error recognition time, the number of saccades, and error correction time.